Scientific Research on Ancient Asian Metallurgy. Proceedings of the Fifth Forbes Symposium at the Freer Gallery of Art - Marisa Gómez González (Ge-conservación, 2013)
Scientific Research on Ancient Asian Metallurgy. Proceedings of the Fifth Forbes Symposium at the Freer Gallery of Art